The effectiveness of stabilization in the supply of information and control systems - Али, Аль-Аммори (Proceedings of National Aviation University (archive), 2009)
In work the questions of increase of efficiency of low-powered and powerful users of electric power are examined by the successive and parallel connecting of impulsive stabilizations.